2018
DOI: 10.16965/ijpr.2017.253
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Effect of Muscle Energy Technique Versus Mulligan Snags on Pain, Range of Motion and Functional Disability for Individuals With Mechanical Neck Pain”. – A Comparative Study

Abstract: Background: Mechanical Neck Pain is very common condition in general population. It still constitutes a major burden on patients in terms of pain, disability, loss of income, and on society in terms of healthcare costs and time of work. A wide variety of treatment protocols for mechanical neck pain are available, however, the most effective management remains an area of debate.Objective: Aim of the study is to compare the effectiveness ofMuscle Energy Technique and Mulligan SNAGS on pain, functional disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Similarly for the second question: “Is MET combined with conventional therapy effective in the treatment of pain, disability and restoration of joint function in acute and chronic non-specific neck pain compared to conventional therapy alone or to the latter combined with another method?”, with regard to patients with neck pain in the acute phase and in the chronic phase, MET is very effective in improving health outcomes such as pain, disability and joint function. The results showed that the combination of conventional therapy, whether it is analgesic instrumental therapy, active stretching or postural education, and MET is very effective with significantly relevant results, in accordance with the guidelines for the treatment of cervical pain that recommend a multifactorial approach in the management of problems related to this pathology [ 34 , 37 , 38 , 42 , 43 , 46 ]. On this assumption, the third question was examined: “Can MET combined with other methods be effective in the treatment of acute and chronic nonspecific neck pain?”.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similarly for the second question: “Is MET combined with conventional therapy effective in the treatment of pain, disability and restoration of joint function in acute and chronic non-specific neck pain compared to conventional therapy alone or to the latter combined with another method?”, with regard to patients with neck pain in the acute phase and in the chronic phase, MET is very effective in improving health outcomes such as pain, disability and joint function. The results showed that the combination of conventional therapy, whether it is analgesic instrumental therapy, active stretching or postural education, and MET is very effective with significantly relevant results, in accordance with the guidelines for the treatment of cervical pain that recommend a multifactorial approach in the management of problems related to this pathology [ 34 , 37 , 38 , 42 , 43 , 46 ]. On this assumption, the third question was examined: “Can MET combined with other methods be effective in the treatment of acute and chronic nonspecific neck pain?”.…”
Section: Discussionsupporting
confidence: 67%
“…Characteristics of included studies are summarized in Table 2 and Table 3 . We used 15 studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] to analyze the effects of MET in patients with non-specific acute neck pain, and 6 studies [ 49 , 50 , 51 , 52 , 53 , 54 ] to analyze the effects of MET in patients with non-specific chronic neck pain. Articles had sample sizes ranging from 28 to 90, contributing to a total sample size of 913 participants, consisting of 527 females and 386 males with a mean baseline age of 18 to 55 years with an average of 32.18 (±7.59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another comparative study was conducted to compare between the effects of MET and mulligan sustained natural apophyseal glides (SNAGs), Tank et al (40) found that both groups were improved after the study intervention by reducing their pain intensity level. Consequently, the study concluded that MET and mulligan SNAGS are equally effective and can be used as alternate treatment along with conventional therapy for treatment of mechanical neck pain.…”
Section: Discussionmentioning
confidence: 99%
“…The results agreed with Joseph and Palappallil, (53) who found that IASTM may be effective in acutely decreasing disability and improving function. Add to this, Tank et al (40) compared between the effects of MET and mulligan SNAGs on neck functional disability level for individuals with mechanical neck pain. The results showed that subjects of both groups were improved after the study intervention by reducing their disability with an equal effect between them.…”
Section: Discussionmentioning
confidence: 99%